Senses and repercussions of student assistance on the eating practices of students from a Brazilian public university during the COVID-19 pandemic - Mota, Lara Vieira Constâncio; Santos, Cláudia Roberta Bocca; Campos, Flávia Milagres (Frontiers in Public Health, 2023)
Student assistance (SA), regulated through the National Student Assistance Program (PNAES), seeks to meet the basic social needs of university students and is inserted in the field of public policies for higher education in federal institutions in Brazil. The program allocates financial resources in order to provide scholarships, housing, food, transport, physical and mental health, and accessibility for disabled students. The present study aims to identify the senses attributed by students of a federal public university to AE and the relationship between SA and their eating practices during the COVID-19 pandemic. A qualitative approach was used. Online questionnaire and focus groups were employed for data collection. The study public consisted of undergraduate students. Descriptive statistics and content analysis were used, opting for thematic analysis, with the support of the MAXQDA software. The core meanings were organized into two categories: (i) food during pandemic and (ii) role of student assistance. A total of 55 responses were obtained, and three focus groups were carried out. About 45% reported that the pecuniary aid offered by the university was the family’s only source of income during the pandemic and 65% used it to buy food. More than half described worsening in food quality, related to food prices. Although no specific evaluation instrument was used, it is plausible to admit that the students experienced a situation of food insecurity, given the uncertainty in regular access to food, the compromised quality of food, and the strategies mobilized to guarantee a minimum amount of food for all members of the family. Among the reported strategies were changing the location and mode of acquisition (receiving donations, buying in groups or in wholesalers) and choosing cheaper genres. Although students consider SA essential for access and maintenance at the university, a sense assigned to SA was the role of “help.” In general, students did not link SA to social rights, as part of public educational policy and as a mechanism for food and nutrition security. SA actions developed during the pandemic were essential for keeping students at the university, also functioning, albeit unintentionally, as a food and nutritional security mechanism.